Single Photon Characterization of (103)-oriented Y Ba2Cu3O7−x Coplanar Waveguide Resonator - Murendranath Patil, Chirag (My University, 2020)
The strong electron-electron correlation makes the cuprate high critical-temperature superconductors (HTS) to behave as unconventional metals, where conventional electron band theory fails to describe the various electronic and magnetic properties of these materials. The most prominent property of HTSs is the superconducting state, whose order parameter symmetry is known to be dominated by a d-wave [1]. Up to date no microscopic theory exists, which could explain the occurrence of superconductivity in these materials. However, the low energy quasiparticle excitation spectrum in these materials is believed to hold key information about the microscopic mechanism leading to the phenomenon of superconductivity in HTS [2]. Superconducting quantum devices are powerful tools to study the quasiparticle excitation spectrum. In fact, a tiny fully developed superconducting gap ( 20μeV ) has been observed by studying the electronic transport in an all-HTS single electron transistor [2]. This experiment unveiled a subdominant complex (s-wave) part in the order parameter besides the d-wave component. A complementary experiment thereof would be the study of relaxation times in a HTS transmon qubit, which should scale with the quasiparticle density of states in the HTS material. The transmon is a type of artificial two-level system (TLS), realized by a capacitively shunted Josephson junction, which is embedded in a superconducting resonator. By probing the microwave spectrum of this two-level system using single photons inside the resonator one can obtain information about quasiparticle induced relaxation processes in the TLS at the qubit transition frequency. Here the resonator acts like a filter towards the environment protecting the transmon from any noise source outside the resonator. Since this device is operated at higher frequencies (around 5 Ghz, which corresponds to an energy of 20μeV ), it is characterized at corresponding low temperatures (T 120mK). The key ingredient of the HTS transmon is the Josephson junction. High quality junctions using HTS can be realized using the bi-epitaxial grain boundary junction. Here, the junction is localized at the interface of (001) oriented YBCO and a (103) oriented YBCO electrode. In order to study quasiparticle induced relaxation processes in a YBCO transmon, all other loss mechanisms such as dielectric losses of the substrate and conductor losses of the YBCO need to be known and characterized in advance. The microwave properties of (001) YBCO films are studied and fairly well understood [3], whereas the microwave properties of (103) YBCO films are yet to be revealed; especially in the low temperature and low power limit (single microwave photon limit). So it is appropriate to study the high frequency dissipation properties of YBCO in the framework of the transmon. By patterning a resonator device using (103) YBCO, its microwave dissipation properties can be investigated within the scope of the transmon design i.e, measuring in the millikelvin temperature and probing in the single photon limit. In this thesis, the resonator is implemented adopting a Coplanar waveguide (CPW) design to understand the different loss mechanisms in the preceding context. The temperature dependence of the resonance frequency and the quality factor (of CPW) is then related to the available models describing various dissipation mechanisms.This work is further directed towards exploring the possibilities of using this CPW resonator as a sensitive magnetic field sensor. This is achieved by studying the variation of the (kinetic) inductance of the superconductor by applying an external magnetic field and also performing some noise measurements to determine its sensitivity. These tasks are the main focus of this thesis work. The first chapter gives a brief introduction to the phenomenological aspects of superconductivity, modeling and design of the coplanar waveguide resonator and properties of a superconducting microwave resonator. Chapter 2 gives a catalogue of the various clean room process steps involved in the fabrication of the resonator followed by the high frequency measurement setup to probe the resonator device. The measured results are analyzed and discussed with conclusion in the final chapters.
Keywords: Transmon, YBCO, High Tc superconductors, d-wave, quasiparticle spectrum analysis, kinetic inductance, london penetration depth, quality factor, coplanar waveguide resonator